2018
DOI: 10.1051/matecconf/201819604061
|View full text |Cite
|
Sign up to set email alerts
|

Composite grouting mortar based on 3D-NKM - nanocrystalline inoculant

Abstract: For the waterproofing of tunnels and the uniform distribution of space between the lining of tunnels and rock, composite injection solutions are used. To improve the physical and mechanical properties of cement composites, the nanoconstruction effect is used, which is possible when using nanoparticles with extended geometry. Nano-additives and nanomodifiers consisting of nanoparticles, both natural and artificial and technogenic, can be used for the production of cement-containing solutions and concretes. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Ускорение гидратации и прочности цементного камня достигается при малых количествах нанодобавок, но при обязательном использовании ультразвука, используемого для предотвращений их агрегации, приводящих к увеличению их размеров при структурообразовании [2][3][4][5][6].…”
Section: Human Activity Safetyunclassified
See 1 more Smart Citation
“…Ускорение гидратации и прочности цементного камня достигается при малых количествах нанодобавок, но при обязательном использовании ультразвука, используемого для предотвращений их агрегации, приводящих к увеличению их размеров при структурообразовании [2][3][4][5][6].…”
Section: Human Activity Safetyunclassified
“…Заключение. Таким образом, в результате проведенных исследований установлено, что наносодержашие добавки ускоряют гидратацию клинкерных составляющих цемента, что приводит к ускорению структурообразования композитных растворов и, как следствие, уменьшению сроков потери их текучести [15][16][17][18][19][20].…”
Section: рисунок 4 -изменение продолжительности схватывания композитнunclassified
“…The main direction of environmental policy is the involvement of production waste in the economic turnover [14][15][16][17][18][19][20][21][22]. There are a number of reasonable directions for the use of production waste -sulfur -in various technologies [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…7). Thus it was found that nano-additives accelerate the hydration of clinker constituents of cement, which leads to acceleration of structure formation of composite mortars and, as a result, to reduction in their flowability loss time [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%